Evaluation of membrane distillation system - Bhindo Velaayudan. (2010)
Membrane distillation (MD) process has been considered as a promising alternative to these conventional separation methods over three decades. However, MD exhibits some potential disadvantages, such as flux decay and distillate contamination due to poor hydrodynamic flow conditions. In this report, one strategy to improve the MD performance has been implemented via optimizing the hollow fiber module configuration.